2019
DOI: 10.1002/etc.4416
|View full text |Cite|
|
Sign up to set email alerts
|

Development and Validation of an Efficient Method for Processing Microplastics in Biota Samples

Abstract: The impacts of microplastics on aquatic ecosystems and biota are gaining attention globally. Although microplastics have been widely detected in biota, there currently are few standardized detection and identification methods. The present study developed a novel one‐step digestion method which was evaluated with mussel and fish samples. This method employed nitric acid and hydrogen peroxide (HNO3:H2O2 = 4:1 by volume) as digestion reagents, which completely digested biota samples <5 g weight within 30 min at 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…This is largely because the methodology used is still under discussion and several different techniques are currently used depending on species and locations (Provencher et al., 2019). Many studies (Hermsen et al., 2018; Rocha‐Santos & Duarte, 2015; Wesch et al., 2016; Yu et al., 2019; Zhang et al., 2019) have claimed that a comprehensive assessment of macro‐ and microplastic ingestion is needed to establish standardized techniques and identify reliable observation methods, which would allow for comparison of results between species and geographical areas. Additionally, the identification of potential gaps will allow for a better understanding of the impact that plastics have at the individual, population, species and ecosystem levels.…”
Section: Introductionmentioning
confidence: 99%
“…This is largely because the methodology used is still under discussion and several different techniques are currently used depending on species and locations (Provencher et al., 2019). Many studies (Hermsen et al., 2018; Rocha‐Santos & Duarte, 2015; Wesch et al., 2016; Yu et al., 2019; Zhang et al., 2019) have claimed that a comprehensive assessment of macro‐ and microplastic ingestion is needed to establish standardized techniques and identify reliable observation methods, which would allow for comparison of results between species and geographical areas. Additionally, the identification of potential gaps will allow for a better understanding of the impact that plastics have at the individual, population, species and ecosystem levels.…”
Section: Introductionmentioning
confidence: 99%
“…Biota samples (mussel and sh) can be digested in a HNO 3 -: H 2 O 2 mixture solution (v/v ¼ 4 : 1) at 50 C for 30 min. 27 In addition, canola oil was used to separate MPs from sediments and the oil was removed with ethanol. 31 We adopted a HNO 27,32,33 the MPs in aquatic organisms can be extracted using a digestion reagent alone and without the residual oil on the surface of MPs.…”
Section: Contamination Prevention and Optimization Of Methods For Ext...mentioning
confidence: 99%
“…Common chemical reagents including acids, alkalies, oxidants and enzymes were used as digestion solutions. [24][25][26][27] Aer otation using reagents such as sodium chloride or sodium iodide, MPs were ltered using membranes. 28,29 However, the oil in food cannot be digested effectively in a short time and MPs are usually oleophilic, which affects the identication of polymers later, and Crichton et al (2017) also demonstrated that oils interfered with the spectrum of MPs.…”
Section: Introductionmentioning
confidence: 99%
“…Digestion methods may involve some form of pre-treatment to increase efficiency of digestion. For example, mussel soft tissue is often extracted from the shell, [80][81][82] thereby reducing the complexity of the matrix for digestion. Once removed from the shells, mussels can be treated similarly to other soft tissue biota (e.g., fish fillet).…”
Section: Digestion Of Samples Containing Biological and Organic Materialsmentioning
confidence: 99%